Homilia in Pentecosten (CPG 6665): A Sermon of Basil of Seleucia - Bishop, Richard W. (Sacris erudiri, 2013)
Primarily on the basis of external evidence, two festal sermons on Pentecost are attributed to the fifth-century bishop and homilist, Basil of Seleucia, by the Clavis Patrum Graecorum (6665 and 6666), an attribution confirmed by Johannes Marius Tevel’s exhaustive study of the manuscript tradition of Basil’s sermons. This article defends the Basilian authorship of CPG 6665 on the basis of internal evidence, pace its first editor, Benedikt Marx, who attributed the sermon to Proclus of Constantinople. The article also assesses a block of material contained both in CPG 6665 and in CPG 4537, a Pentecost sermon of Pseudo-Chrysostom, as well as a second block of material contained both in CPG 6665 and in CPG 4061, an encomium on six apostles, assigned to Ephrem Graecus. Arguments are advanced for the priority of CPG 6665 in both cases, but left open is the possibility that neither block of material is an original composition of Basil. An appendix to the article contains a demonstration of the Basilian authorship of CPG 6666 on the basis of internal evidence.